Corruption and Electoral Processes in Latin America - Nieto Flores, Nubia Zulma (2024)
Electoral processes are one of the most important pillars of democracy. Transparent, fair and representative elections are the basis of the Western democracies. However, holding electoral processes does not necessarily guarantee the establishment and exercise of the democracy. Elections based on intimidation, threats, insecurity, fear, violence, harassment, fraud, vote buying, abuse, manipulation and exploitation of vulnerable conditions are threats to democracy and an expression of the exercise of corruption. Latin America in recent years has been characterized by adopting democratic governments. In recent decades, almost all countries in the region have managed to overthrow authoritarian, military and dictatorial governments. However, the democratic exercise of citizens in local, regional and national elections is often questioned due to the lack of integrity and transparency of the processes. In this context, this article aims to analyze the role of corruption in electoral processes in Latin America in the last decades. The hypothesis that guides this work is based on the assumption that holding elections does not necessarily guarantee the exercise of democracy, since corruption permeates electoral processes. The text uses qualitative and based on data provided by national and international institutions, analysis and case studies, global reports and journalistic notes, as well as historical sources. The text is divided into three sections. The first exposes some basic concepts of electoral democracy and the threat of corruption. The second presents the effects of corruption materialized in electoral fraud, vote buying, disappearance of ballot boxes, manipulation in digital systems, application of Artificial Intelligence, sponsorship of criminal groups towards a certain candidate, use of criminal forces to intimidate, murder, destabilize electoral processes. The third offers some examples of highly questioned electoral processes in Latin America, and finally some conclusions are made, leaving the door open to future studies that can contribute to reduce the risks of corruption in electoral processes in the Latin American region and help mature the young democracy.